Surgery Significantly Improves Neurocognition, Sleep, and Blood Pressure in Primary Hyperparathyroidism: A 3-Year Prospective Follow-Up Study - Storvall, Sara; Ryhänen, Eeva M.; Heiskanen, Ilkka; Sintonen, Harri; Roine, Risto P.; Schalin-Jäntti, Camilla (Hormone and Metabolic Research, 2017)
Surgery for primary hyperparathyroidism (PHPT) improves health-related quality of life (HRQoL), but it is unclear whether the effects are sustained after medium-term (>2 years) follow-up, and whether the results on some or all dimensions of HRQoL will reach that of the general population. We performed a follow-up of HRQoL on average 3.3 years after surgery for PHPT using the 15D in our patient cohort (n=124) and compared the results to those of an age- and gender-standardized general population (n=1099). We studied self-reported blood pressure and current medications; new comorbidities were retrieved from electronic patient records. A total of 104 (83%) patients [eight with serum calcium (1.34–1.46 mmol/l)] returned the questionnaires. After a follow-up of 3.3 years (range 23 to 55 months), systolic and diastolic blood pressure had decreased significantly compared to baseline (the situation before surgery, p<0.001). Thirty-four (33%) had acquired a new diagnosis (range 1–7), the most common being cardiovascular disease and cancer. Mean 15D score was significantly better compared to baseline (p<0.001), the dimensions of sleeping, mental function, discomfort and symptoms, and depression had further improved (p<0.01), and no longer differed from that of the general population. In PHPT, after >2 years follow-up, surgery improves blood pressure and restores neurocognitive function and sleep to the level of the general population. The improvements observed in overall HRQoL at one year after surgery are sustained, but overall HRQoL does not reach that of the general population.
Keywords: primary hyperpaparathyroidism; surgery; health-related quality of life; hypertension; medication; neurocognitive function